2016
DOI: 10.1063/1.4968172
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of mesoporous 4H-SiC prepared by anodic electrochemical etching

Abstract: Porous silicon carbide was fabricated from n-type 4H-SiC substrates via anodic electrochemical etching in HF/ethanol solution and suspended in ethanol after ultrasonication. We observed three photoluminescence bands: two at wavelengths of 303 nm and 345 nm were above the bulk bandgap and one at 455 nm was below the bulk bandgap. These blue-shifted and red-shifted emission processes reveal the interplay between quantum confinement, surface states, and band edge related optical transitions. We propose a model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Likewise, one possible explanation of the photoluminescence properties of porous SiC is related to the diversity in surface states 21 ; therefore, it is important to know the chemical groups of the internal surface on the porous SiC. It has been demonstrated that the surface of porous SiC contains a wide variety of different chemical groups: carboxylic acid groups, silane groups, hydrocarbon fragments and hydroxyl groups 20,27,28 . Since it is important to understand the underlying physics of luminescence phenomena for its engineering applications, it is critical to carry out a thorough analysis of the carrier recombination mechanisms in porous SiC structures.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, one possible explanation of the photoluminescence properties of porous SiC is related to the diversity in surface states 21 ; therefore, it is important to know the chemical groups of the internal surface on the porous SiC. It has been demonstrated that the surface of porous SiC contains a wide variety of different chemical groups: carboxylic acid groups, silane groups, hydrocarbon fragments and hydroxyl groups 20,27,28 . Since it is important to understand the underlying physics of luminescence phenomena for its engineering applications, it is critical to carry out a thorough analysis of the carrier recombination mechanisms in porous SiC structures.…”
Section: Introductionmentioning
confidence: 99%
“…The exact nature of the etched D‐Por‐SiC surface has not yet been ascertained, however previous work indicates that the electrochemically etched SiC surface is likely to show Si depletion and be C‐rich . Here, an amorphous layer approximately 1 nm thickness exists on the etched surface surrounding the pore in D‐Por‐SiC . The chemical composition of this layer is not similar to that of the crystalline face of the bulk crystal.…”
Section: Resultsmentioning
confidence: 97%
“…The formation of an amorphous layer between the crystalline SiC and pore has been reported previously, and the formation of which was linked to the etching conditions. Peaks related to silicon oxycarbide and SiO 2 were observed in XPS spectra and these may be attributed to the existence of an amorphous layer at the surface that influences the oxidation of D‐Por‐SiC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon carbide is a very important semiconductor material [1, 2] which has more than 200 poly-types [3] and has great properties which make it an attractive material to be used for applications in extreme environment [4, 5, 6]. These interesting properties include high strength, high hardness, and low thermal expansion [7, 8, 9], and it has been used in high-temperature applications because of its high thermal conductivity [10, 11, 12] which is 3.6 W/cm-K for 3C–SiC, and 4.9 W/cm-K for 4H–SiC and 6H–SiC [13].…”
Section: Introductionmentioning
confidence: 99%